GLIM criteria using NRS-2002 and MUST as the first step adequately diagnose the malnutrition in Crohn’s disease inpatients: A retrospective study - Wang, Meng; Guo, Qin; Liu, Hong; Liu, Min; Tang, Chenyi; Wu, Jinru; Feng, Guo; Wu, Wei (Frontiers in Nutrition, 2023)
Objective The Global Leader Initiative on Malnutrition (GLIM) criteria have been recommended for malnutrition diagnosis recently, for which the first step is malnutrition risk screening with any validated tool. This study aims to investigate the incidence of nutritional risk and malnutrition in Crohn’s disease inpatients and compare the suitability of Nutritional Risk Screening 2002 (NRS-2002) and Malnutrition Universal Screening Tool (MUST) as the first-step screening tool for GLIM criteria. Methods We retrospectively analyzed the clinical data of Crohn’s disease inpatients in our hospital from August 2016 to December 2019. NRS-2002 and MUST were used for nutritional screening at the time of admission. GLIM and Patient Generated-Subjective Global Assessment (PG-SGA) were used for malnutrition assessment, respectively. Patients without nutritional risk screened by NRS-2002 but with malnutrition risk screened by MUST were especially screened out. The appendicular skeletal muscle mass index (ASMI), fat-free mass index (FFMI), body fat percent (BFP), and body cell mass (BCM) were measured by the Biospace Inbody S10 composition analyzer. Results A total of 146 Crohn’s disease patients were enrolled, of which 62.3 and 89.7% had nutritional or malnutrition risk according to NRS-2002 and MUST, respectively. The prevalence of malnutrition assessed by GLIM was 59.6% (87 cases) and 82.2% (120 cases) when NRS-2002 and MUST were used as the first step of GLIM respectively. Meanwhile, 99 patients (67.8%) had malnutrition when assessed by PG-SGA. There were 41 patients who were not at nutritional risk according to NRS-2002 but were at malnutrition risk determined by MUST. At last, 33 patients were GLIM-defined, and 16 patients were PG-SGA-defined malnutrition among the 41 patients. Conclusion The nutritional risk or malnutrition is common in Crohn’s disease inpatients. It is recommended to use a variety of nutritional assessment tools for Crohn’s disease inpatients. MUST can be used as a good supplement for the patients with a score of NRS-2002 lower than 3 in order to decrease the miss rate of GLIM-defined malnutrition.